Predicting thermal performance of fired clay bricks lightened by adding organic matter: Improvement of brick geometry. (May 2015) - Aouba, Laila; Coutand, Marie; Perrin, Bernard; Lemercier, Hervé
Fired clay masonry bricks adapt to a variety of constraints during use. Through their mass, these products provide thermal inertia and thus a good indoor climate. Thanks to their thermal insulation properties, they help to minimize heating and cooling costs. The brick industry allows different by-products to be added into the clay mixture at the beginning of the industrial cycle, and the incorporation of organic matter improves thermal insulation while reducing the weight of the bricks. This article presents an experimental and numerical method for determining the thermal resistance of fired clay bricks containing residue of wheat straw. As their thermal conductivity reaches a value 35% lower than that of clay without organic matter, the thermal transmittance of such bricks can be improved by more than 20% relative to existing values.